PENGAYAAN PENGETAHUAN MASYARAKAT SEKITAR HUTAN TENTANG REVITALISASI PANGAN LOKAL DALAM MENDUKUNG FOOD SECURITY - Nanlohy, Lona H.; Maruapey, Azis; Hahury, Sanny; Saeni, Fajrianto; Kamaluddin, Kamaluddin; Lestaluhu, Rajab; Wahid, Bustamin; Maipauw, Niny J.; Saeni, Agil (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
The program to enrich the community's knowledge about local food is an effort to increase families' knowledge and awareness of nutritional needs, as this program provides education that focuses on the importance of consuming a variety of nutritious, balanced foods, utilizing the potential of local food to support family resilience and nutrition. The objective of this activity is to enrich the knowledge of communities living around forests about the revitalization of local foods in supporting food security for communities in Arus Village, Maybrat Regency. This community service approach uses a participatory approach in the form of socialization and Focus Group Discussions (FGD). The community is now more open to utilizing local food in their daily diet, which contributes to their health and well-being. However, challenges in the accessibility of local food ingredients still need to be addressed to ensure the sustainability of the Food Security program. Overall, this Knowledge Enrichment program not only provides knowledge but also empowers the community to implement better nutritional practices, which in turn can improve their quality of life.